PELATIHAN JURNALISME WARGA DAN MANAJEMEN KONTEN UNTUK MENINGKATKAN PUBLISITAS MEDIA SOSIAL DESA ADOBALA - Sukaemi, Linda Handayani; Sulistyaningtyas, Tri; Suryani, Yani; Siregar, Harifa Ali Albar; Kamila, Sira (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
In the era of information technology, publicity has become an important component in assessing the progress of a village. Increasing the publicity of a village is not only the responsibility of the village public relations officer but also the residents who live in the village. Adobala Village, Kelubagolit Sub-district, East Flores Regency, East Nusa Tenggara, has a public relations officer who is actively promoting the village. The village already has adequate publication channels. However, local residents still need digital literacy to improve the publicity of the village from the residents' perspective. Therefore, citizen journalism training is very effective in improving the publicity of the village through the village's social media channels and social media of the community that is active in village activities. Based on the results of the study, digital literacy regarding citizen journalism and content management in Adobala Village, has increased the literacy of residents and village public relations officers regarding the creation of village content. This increase in literacy can be seen from the increased publicity of Adobala Village through the improved quality of content and number of views on the @adobaladesa social media account on Instagram. There is a variety of artificial intelligence (AI)-based video content, national holiday content, and local cultural content that increases views on social media @adobaladesa. ABSTRAK Pada era teknologi informasi publisitas menjadi komponen yang penting dalam penilaian kemajuan sebuah desa. Peningkatan publisitas desa tidak hanya menjadi tanggung jawab humas desa tetapi juga para warga. Desa Adobala, Kecamatan Kelubagolit, Kabupaten Flores Timur, Nusa Tenggara Timur memiliki media sosial dengan publisitas yang masih terbatas. Desa sudah memiliki kanal-kanal publikasi tetapi konten yang disajikan masih sangat formal dan tidak beragam. Warga sekitar masih memerlukan literasi digital untuk meningkatkan publisitas desa dari perspektif warga. Oleh sebab itu, pelatihan jurnalisme warga dan manajemen konten dibutuhkan untuk meningkatkan keragaman jenis dan variasi konten. Berdasarkan hasil penelitian, literasi digital mengenai jurnalisme warga dan manajemen konten di Desa Adobala memberikan peningkatan literasi pada warga dan humas desa mengenai pembuatan konten desa. Peningkatan literasi ini terbukti melalui peningkatan publisitas Desa Adobala melalui peningkatan kualitas konten dan jumlah views pada media sosial @adobaladesa di Instagram. Terdapat variasi konten video berbasis artificial intelligence (AI), konten peringatan hari besar nasional, dan konten budaya lokal yang meningkatkan views di media sosial @adobaladesa.